Implementation of the Halal Certification Acceleration Policy to Increase the Competitiveness of the Indonesian Halal Industry - Najla Shafaa Kamila; Refani Nafi Sara; Deva Sukmawati; Moh. Az Fahani Zain; Ersya Faraby (Penerbit Hellow Pustaka, 2025)
Indonesia aspires to become the world's leading producer and exporter of halal products, but the implementation of policies to accelerate halal certification still faces various challenges, especially among UMKM. The main obstacles include limited resources, low halal literacy, certification costs, and a process that is considered complicated. As a result, Indonesia remains a major importer of halal products despite its high domestic and global market potential. This study aims to analyze the implementation of the halal certification acceleration policy in order to improve the competitiveness of the halal industry in Indonesia. The method used is qualitative with a literature review approach based on secondary data. The results of the study show that the acceleration of certification is not fully proportional to the increase in the competitiveness of Indonesian halal product exports.